2007
DOI: 10.1179/143307507x246611
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters on hydrothermal formation of magnesium borate hydroxide nanowhiskers

Abstract: Uniform magnesium borate hydroxide [MgBO 2 (OH)] nanowhiskers with a diameter of 20-60 nm and an aspect ratio of 10-70 were synthesised via a coprecipitation/hydrothermal reaction route, using NaOH, MgCl 2 and H 3 BO 3 as the reactants. The experimental results indicated that the control of the Mg/B/Na molar ratio at 2 : 3 : 4, the decrease in the NaOH concentration from 2?0 to 0?33 mol L -1 , the increase in the hydrothermal temperature from 160 to 240uC and the prolongation of the hydrothermal reaction time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…The interplanar spacings of 0.597 nm detected from the legible lattice fringes along the axis of the nanowire (Fig. 3b 1 ) was quite similar to that of the (200) planes of the standard MgBO 2 (OH), indicating the preferential growth direction of the nanowires parallel to the (200) planes, in agreement with that of the MgBO 2 (OH) nanowhiskers along the c -axis [38] and also the growth habit of the natural szaibelyite (MgBO 2 (OH)) [40]. The statistic data showed that the MgBO 2 (OH) nanowires had a length of 0.5–9.0 μm (approx.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…The interplanar spacings of 0.597 nm detected from the legible lattice fringes along the axis of the nanowire (Fig. 3b 1 ) was quite similar to that of the (200) planes of the standard MgBO 2 (OH), indicating the preferential growth direction of the nanowires parallel to the (200) planes, in agreement with that of the MgBO 2 (OH) nanowhiskers along the c -axis [38] and also the growth habit of the natural szaibelyite (MgBO 2 (OH)) [40]. The statistic data showed that the MgBO 2 (OH) nanowires had a length of 0.5–9.0 μm (approx.…”
Section: Resultsmentioning
confidence: 59%
“…Since low concentration of the reactants, relatively long reaction time and high temperature favored the synthesis of MgBO 2 (OH) nanowhiskers with a longer size and higher aspect ratio [38], less amount of NaOH solution (4 mol L −1 ), in other words, lower initial concentration of NaOH (0.17 mol L −1 ) was employed in the room temperature coprecipitation so as to further increase the length and aspect ratio of the hydrothermal product, with the molar ratio of Mg:B:Na and also total volume of the mixed solution unchanged. The resultant well dispersed uniform nanowires (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the parameters in course of thermal conversion, the hydrothermal procedure [49] determined the 1D morphology of the MgBO 2 (OH) nanowhiskers and could further influence the morphology of the final calcined Mg 2 B 2 O 5 nanowhiskers. Hydrothermal conditions are favorable for the formation of the unique crystal structure containing water in lattice; the unique structure can contribute to porous structure by dehydration and the active porous whiskers can finally form high-crystallinity nanowhiskers via recrystallization.…”
Section: Resultsmentioning
confidence: 99%